The MODE Model and Its Implications for Studying the Media - Rhodes, Nancy and Fazio, Russell H (Media psychology, 2015)
Attitude and norm accessibility influence social behavior and how messages are processed. The Motivation and Opportunity as DEterminants (MODE) model is offered as a framework for understanding when attitude and norm accessibility should play an important role in social behavior. In this article, we outline the MODE model and consider the implications of the MODE model for both how people process media messages and the consequences of media messages.
https://katalog.adlr.link/Record/ai-68-OLC1960747622